Energy transfer to a stable donor suppresses degradation in organic solar cells - Weu, Andreas; Lami, Vincent; Paulus, Fabian; Vaynzof, Yana (Advanced functional materials, 2020)
Despite many advances toward improving the stability of organic photovoltaic devices, environmental degradation under ambient conditions remains a challenging obstacle for future application. Particularly conventional systems employing fullerene derivatives are prone to oxidize under illumination, limiting their applicability. Here, the environmental stability of the small molecule donor DRCN5T together with the fullerene acceptor PC70BM is reported. It is found that this system exhibits exceptional device stability, mainly due to almost constant short-circuit current. By employing ultrafast femtosecond transient absorption spectroscopy, this remarkable stability is attributed to two separate mechanisms: 1) DRCN5T exhibits high intrinsic resistance toward external factors, showing no signs of deterioration. 2) The highly sensitive PC70BM is stabilized against degradation by the presence of DRCN5T through ultrafast, long-range energy transfer to the donor, rapidly quenching the fullerene excited states which are otherwise precursors for chemical oxidation. It is proposed that this photoprotective mechanism be utilized to improve the device stability of other systems, including nonfullerene acceptors and ternary blends.
First published: 20 November 2019
Falsche Schreibweise bei der Autorin Yana Vaynzof
Gesehen am 18.01.2021